Head games: A systematic review and meta-analysis examining concussion and head impact incidence rates, modifiable risk factors, and prevention strategies in youth tackle football - Pankow, M. P.; Syrydiuk, R. A., Kolstad, A. T.; Hayden, A. K.; Dennison, C. R.; Mrazik, M.; Hagel, B. E.; Emery, C. A. (Sports Medicine, 2022)
Objectives: The aims were to (1) examine the rates and mechanisms of concussion and head impact in youth football (high school level or younger); (2) identify modifiable risk factors for concussion and head impact; and (3) evaluate the effectiveness of prevention strategies in tackle football at any level. Methods: Nine databases (CINAHL Plus with Full Text; Cochrane Central Register of Controlled Trials; EMBASE; ERIC; Ovid MEDLINE(R) and Epub Ahead of Print, In-Process & Other Non-Indexed Citations and Daily; ProQuest Dissertations & Theses Global Database; PsycINFO; Scopus; and SPORTDiscus with Full Text) were searched using the search strategy focusing on four main concepts: concussion/head impact, tackle football, modifiable risk factors, and primary prevention. Two reviewers completed title, abstract, and full-text screening as well as risk of bias assessment (using the Downs and Black checklist), with a third author available to resolve any disagreements. Main Results: After removing duplicates, 1911 articles were returned. Fifty-eight articles were included in the review and 20 in the meta-analysis. The overall combined rates of concussion (including game and practice-related concussion) based on the meta-analysis were 0.78 concussions/1000 athlete exposures [95% confidence interval (CI) 0.67-0.89] for high school football (ages 13-19) and 1.15 concussions/1000 athlete exposures (95% CI 0.89-1.41) for minor football players (ages 5-15). There is evidence that contact training and practice contact restrictions have reduced the rate of head impacts and concussion. Heads Up Football (an intervention focused on coach education and contact training) has been shown to reduce the rate of concussion by 32% and head impacts by 38% amongst high school football players. Limiting contact practices in high schools to 2 days per week reduced practice head impacts per player-season by 42%, and limiting full contact in practice to 75 min per week in the second week of the season and 60 min in week 3 and beyond resulted in a 54% decrease in the practice-related concussion rate (p = 0.003). Conclusions: This review identified a critical need for interventions to address the high rates of concussion and head impact in youth football. To date, contact training and contact restrictions have the strongest evidence supporting their effectiveness at reducing these rates. Future research should use consistent concussion definitions and validated injury surveillance systems, and ensure complete reporting of participant characteristics and sampling details.